Epicillin: Experimental Chemotherapy, Pharmacodynamics, and Susceptibility Testing - Gadebusch, H. (1971)
Epicillin exhibits excellent therapeutic activity when administered orally or subcutaneously to mice infected with a variety of pathogenic bacteria. These included single strains of Streptococcus pyogenes, non-penicillinase-producing Staphylococcus aureus, Proteus mirabilis, Escherichia coli, Salmonella schottmuelleri, and Pseudomonas aeruginosa, strains of microorganisms selected as typical of those that frequently cause serious clinical infections. In oral chemotherapeutic comparisons of tetracycline, chloramphenicol, cephalexin, ampicillin, and epicillin, the latter, with but minor exceptions, exhibited activity comparable to that of most of the other antibiotics studied. Oral administration to mice of a loading dose of epicillin or ampicillin resulted in similar peak blood levels and decay curves. The concentration in urine and the excretion rates were significantly higher in epicillin than in ampicillin-treated animals. Presumptive evidence suggests that the inter-pretation of zone diameters obtained with 10-μg epicillin discs should be the same as is used for 10-μg ampicillin discs.